2017
DOI: 10.1186/s12906-017-1764-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of total flavonoids of Spatholobus suberectus Dunn on PCV2 induced oxidative stress in RAW264.7 cells

Abstract: BackgroundThis study was carried out to investigate the effect of total flavonoids of Spatholobus suberectus Dunn (TFSD) on PCV2 induced oxidative stress in RAW264.7 cells.MethodsOxidative stress model was established in RAW264.7 cells by infecting with PCV2. Virus infected cells were then treated with various concentrations (25 mg/ml, 50 mg/ml and 100 mg/ml) of TFSD. The levels of oxidative stress related molecules (NO, ROS, GSH and GSSG) and activities of associated enzymes (SOD, MPO and XOD were analyzed us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 56 publications
0
30
0
Order By: Relevance
“…PCV2 has been reported to induce mitochondrial apoptosis in PK-15 cells [27,28]. MMP is recognized as a marker of mitochondrial statement.…”
Section: Discussionmentioning
confidence: 99%
“…PCV2 has been reported to induce mitochondrial apoptosis in PK-15 cells [27,28]. MMP is recognized as a marker of mitochondrial statement.…”
Section: Discussionmentioning
confidence: 99%
“…Medical research shows that curcumin has low toxicity, little adverse reactions and multiple therapeutic effects, such as anti-inflammatory [29], anti-oxidative [30], anti-H9N2 influenza virus [31], dengue virus [32], hepatitis C virus [33] and so on. Zhang et al demonstrated that PCV2 Cap could induce mitochondrial apoptosis of PK-15 and PAM cells by interfering with Ca 2+ homeostasis, down-regulating MMP and increasing intracellular ROS [7]; Lin et al found that PCV2 induced mitochondrial apoptosis of PCV2 infected PK-15 cells and 293 T cells by increasing the activities of caspase-3 and caspase-9 and accelerating the release of cytochrome C (Cyto C) from mitochondria to cytoplasm [34]; After PCV2 infected RAW264.7 cells, stress-related molecules such as ROS production and NO secretion were significantly increased [35]; Previous studies have shown that PCV2 infection promotes the accumulation of ROS, which in turn inhibits the replication of PCV2 through the NF-κB pathway [36]. Therefore, we hypothesized that the experimental compounds could inhibit the mitochondrial apoptosis of PK-15 cells induced by PCV2 infection via acting on mitochondrial membrane potential.…”
Section: Discussionmentioning
confidence: 99%
“…Lin et al proved that the PCV2 could up-regulate MMP and induce apoptosis through mitochondrial pathway [34]; Chen et al proved the accumulation of ROS and interference with mitochondrial function were demonstrated in RAW264.7 cells infected with PCV2 [35,36]. Mitochondria have a central role in cell apoptosis.…”
Section: Discussionmentioning
confidence: 99%